Dual Gene Delivery Reagents From Antiproliferative Alkylphospholipids for Combined Antitumor Therapy - Gaillard, Boris; Remy, Jean-Serge; Pons, Françoise; Lebeau, Luc (Frontiers in Chemistry, 2020)
Alkylphospholipids (APLs) have elicited great interest as antitumor agents due to their unique mode of action on cell membranes. However, their clinical applications have been limited so far by high hemolytic activity. Recently, cationic prodrugs of erufosine, a most promising APL, have been shown to mediate efficient intracellular gene delivey, while preserving the antiproliferative properties of the parent APL. Here, cationic prodrugs of the two APLs that are currently used in the clinic, miltefosine and perifosine, are investigated and compared to the erufosine prodrugs. Their synthesis, stability, gene delivery and self-assembly properties, and hemolytic activity are discussed in detail. Finally, the potential of the pro-miltefosine and pro-perifosine compounds M E12 and P E12 in combined antitumor therapy is demonstrated using pUNO1-hTRAIL, a plasmid DNA encoding TRAIL, a member of the TNF superfamily. With these pro-APL compounds, we provide a proof of concept for a new promising strategy for cancer therapy combining gene therapy and APL-based chemotherapy.